Analyzing the Meaning of Tundu Tenang Curup Poetry: A Semiotic Approach - Yohanes Tresno Kurnianto; Mirsa Umiyati (RETORIKA: Jurnal Ilmu Bahasa, 2025)
This research investigates the semiotic dimensions of the Manggarai poem Tundu Tenang Curup using Ferdinand de Saussure’s semiotic theory, focusing on icons, symbols, and indices to explore the interplay between signifiers and the signified. Employing a descriptive qualitative method through document analysis, the study reveals that the poem encapsulates cultural values such as communal harmony, resilience, and protection from malevolent influences, deeply rooted in traditional ceremonies like Cear Cumpe and Wuat Wa’i. These findings highlight the poem’s role in embodying and transmitting Manggarai's cultural heritage. Moreover, translations into Indonesian and English broaden the poem’s accessibility and illuminate its literary and cultural significance. This research underscores the critical role of semiotic analysis in understanding indigenous literature and advocates for the preservation of Manggarai cultural traditions.